Pedagogy, Future and Freedom: The School Institution as Represented by Teachers, Parents and Students - Denize Cristina De Oliveira; Ignez Salas Martins; Frida Marina Fischer; Celso Pereira Sá; Antonio Marcos Tosoli Gomes Gomes; Sergio Corrêa Marques (Psicologia, 2004)
Teachers, parents and students’ social representations of the fundamental and medium teaching in the school institution were studied in two districts of the state of São Paulo, Brazil. Data collection was accomplished through semi-structured interviews with 84 teachers and 40 parents, and 34 focus-group sessions with adolescents from 11 to 18 years old. Data were analysed by using the softwares ALCESTE 4.5, for lexical analysis, EVOC, for the analysis of free evocations, and SIMI, for similitude analysis. Results showed different conceptions on the part of each studied group, as a function of the potentialities attributed to the school institution. For teachers, school was seen as a “pedagogic locus”; parents saw the teaching institution as the “only future possibility” for children of popular classes; and students represented the school as the possibility of “freedom through knowledge”. It is then concluded that the processes of social representations construction in the different groups have as their results sharply different images about the school institution, which correspond to the daily practices of those subjects and so legitimate their respective actions of approval or rejection of that institution.